Nucleotropic doxorubicin nanoparticles decrease cancer cell viability, destroy mitochondria, induce autophagy and enhance tumour necrosis - Friedhuber, A.; Chandolu, V.; Manchun, S.; Donkor, O.; Sriamornsak, P.; Dass, Crispin (Blackwell Publishing Ltd, 2015)
Objective: Doxorubicin (Dox) is used clinically against various neoplasias, but suffers from serious side effects, and for the past three decades, this shortcoming has spurred research towards finding better drug delivery systems (DDSs) for this frontline drug. Methods: A non-targeted nucleotropic Dox-loaded nanoparticle (DNP) DDS is described, which has a simple chemical design, is easy to formulate and administer, is inexpensive, non-biohazardous and may prove to be useful clinically. Key findings: The DNP formulated via vortex-assisted complex coarcevation enhanced (300-fold) cell-inhibitory activity of the drug in a panel of human cancer cells (osteosarcoma, breast, prostate and colorectal cancer) and enhanced (10-fold) efficacy against osteosarcoma (OS) in vivo. The slow-release DNPs localised to the endoplasmic reticulum disrupted the mitochondria and entered the nucleus. Prominent cytosolic vacuolisation, budding off of portions of the cytoplasm, both suggestive of autophagy, were observed. Mice that were administered with DNPs intratumorally had the smallest tumours at the end of the study, with more necrotic hotspots. Conclusion: This promising nucleotropic DDS enhances the cell delivery and activity of Dox against a variety of human cancer cell lines and in OS tumours in mice.